Verses on Slaves in the Holy Quran between Rhetorical Indications and Legislative Purpose - Al-Hurirat , Ali Abdullah Ahmed (Dirasat: Shari’a and Law Sciences, 2020)
This study dealt with an important Qur’anic theme, namely, the verses of slavery and bondmaids in the Holy Qur’an. The researcher induced this concept from the verses of the Qur’an and the contexts in which they were presented. The researcher attempted to respond to the suspicions that cannot stand in front of this Qur’anic legislation that dealt with a phenomenon that existed before it came; this legislation conquered it during a brief period of complete descent of the Qur’an. The study used the inductive method by collecting the verses talking about slaves. It also used the deductive method by studying the subject from its linguistic, explanatory, and fiqh aspects. This study addressed the suspicions that aimed to undermine Islam in relation to the concept of slavery by presenting the contexts that referred to slavery in the Holy Quran and refuting those suspicions. The study also confirmed the position of the Holy Quran on the promotion of freedoms and the narrowing of the circle of slavery and the bondmaids. It also concluded that the categorical prohibition of the issue of slaves is part of the legitimate policy that can be used in the exchange of prisoners. The verses of manumission and Maktabah also indicate Islam’s keenness on freedom and the pursuit of achieving it and its rejection of slavery and its forms.